2016
DOI: 10.3109/01612840.2015.1092187
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention with Physical Activity and Lifestyle Counseling Improves Health-Related Quality of Life and Shows Small Improvements in Metabolic Risks in Persons with Psychosis

Abstract: General purpose: To study the effects of a lifestyle intervention on health-related quality of life (HRQoL) and metabolic risk factors in persons with psychosis. Methodology: A longitudinal intervention study with a matched reference sample. Results: HRQoL measured by the EQ-VAS improved from 57.6 to 63.3 (17.8) in the intervention group (p=0.05). The HDL cholesterol concentration increased from 1.03 to 1.11 (0.19) mmol/l in the intervention group (p=0.02). There was no significant change in body weight. Concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A recent study indicated that a lifestyle intervention based on group meetings improved the quality of life among patients with psychosis and effected small improvements in metabolic risk factors (Wardig et al . ). In the present study, the MANSA scale used to measure quality of life showed a significant postinterventional improvement of 4 points.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study indicated that a lifestyle intervention based on group meetings improved the quality of life among patients with psychosis and effected small improvements in metabolic risk factors (Wardig et al . ). In the present study, the MANSA scale used to measure quality of life showed a significant postinterventional improvement of 4 points.…”
Section: Discussionmentioning
confidence: 97%
“…, Wardig et al . ). However, much more integrated health care is needed to tackle the disparities in physical health between people with and without mental illness (Moore et al .…”
Section: Introductionmentioning
confidence: 97%
“…For example, programs of physical exercise have shown to reduce psychotic symptoms (Beebe et al, 2005;Rimes et al, 2015;Scheewe et al, 2013), depressive symptoms (Acil et al, 2008;Scheewe et al, 2013), anxiety (Wipfli et al, 2008) and stress (Hoffmann et al, 2005) and improved quality of life was found after a nutritional intervention (Evans et al, 2005) and a psycho-educational weight control program (Mauri et al, 2008). However, symptomatic stability or unchanged quality of life were also reported (Ball et al, 2001;Brar et al, 2005;Forsberg et al, 2010;Heggelund et al, 2011;Kwon et al, 2006;Poulin et al, 2007;Wärdig et al, 2016). Drawing firm conclusions about the effect of lifestyle interventions on mental health is complicated due to small sample sizes (Acil et al, 2008;Ball et al, 2001;Beebe et al, 2005;Evans et al, 2004;Forsberg et al, 2010;Heggelund et al, 2011;Kwon et al, 2006;Mauri et al, 2008) or the lack of a control group (Daumit et al, 2011;Hoffmann et al, 2005;Richardson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%